2018
DOI: 10.3727/096504017x15009778205068
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Vimentin Is Critical to Promote a Metastatic Potential of Cholangiocarcinoma Cells

Abstract: Cholangiocarcinoma (CCA) is a highly metastatic tumor, and the majority of patients with CCA have a short survival time because there are no available effective treatments. Hence, a better understanding regarding CCA metastasis may provide an opportunity to improve the strategies for treatment. A comparison study between the highly metastatic cells and their parental cells is an approach to uncover the molecular mechanisms underlying the metastatic process. In the present study, a lung metastatic CCA cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The M0725 antibody from Dako detects a band at 54 kDa on Western blots of human mesenchymal stromal cell lysates (Talele, Fradette, Davies, Kapus, & Hinz, ). Treatment of a human cholangiocarcinoma cell line with siRNA against vimentin suppressed immunoblot and immunofluorescent signals with this antibody (Saentaweesuk et al, ). The two anti‐vimentin antibodies used yielded a similar expression profile.…”
Section: Methodsmentioning
confidence: 99%
“…The M0725 antibody from Dako detects a band at 54 kDa on Western blots of human mesenchymal stromal cell lysates (Talele, Fradette, Davies, Kapus, & Hinz, ). Treatment of a human cholangiocarcinoma cell line with siRNA against vimentin suppressed immunoblot and immunofluorescent signals with this antibody (Saentaweesuk et al, ). The two anti‐vimentin antibodies used yielded a similar expression profile.…”
Section: Methodsmentioning
confidence: 99%
“…During the process of EMT, carcinoma cells lose their epithelial characteristics, including polarity and cell-cell adhesions, and acquire a mesenchymal phenotype to obtain an invasive capacity [50]. Several studies have indicated that the expression of MMP-2 and MMP-9 is associated with EMT, and vimentin is often used as a marker of mesenchymally derived cells or cells undergoing EMT during both normal development and metastatic progression [51,52]. However, the STAT3 signaling pathway has been shown to be involved in tumor EMT [53].…”
Section: Discussionmentioning
confidence: 99%
“…CCA cell lines, KKU-213 and KKU-214, were established from a primary tumor of CCA patients and deposited in JCRB. KKU-213L5 and KKU-214L5 were the lung metastatic CCA cell lines derived from KKU-213 and KKU-214 as previously described [27,28]. All cell lines were cultured in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum (FBS) and antibiotic-antimycotic in a 5% CO 2 incubator at 37 • C.…”
Section: Cholangiocyte and Cca Cell Linesmentioning
confidence: 99%